Effects of Tocotrienol Supplementation on Hair Growth in Human Volunteers - Lim Ai Beoy; Wong Jia Woei; Yuen Kah Hay (Tropical Life Sciences Research, 2010)
Studies have shown an association between oxidative stress and alopecia. Patients with alopecia generally exhibit lower levels of antioxidants in their scalp area as well as a higher lipid peroxidation index. Tocotrienols belong to the vitamin E family and are known to be potent antioxidants. Hence, a study was conducted to investigate the effect of tocotrienol supplementation on hair growth in volunteers suffering from hair loss. Twenty one volunteers were randomly assigned to orally receive 100 mg of mixed tocotrienols daily while 17 volunteers were assigned to receive placebo capsule orally. The volunteers were monitored for the number of hairs in a pre-determined scalp area as well as the weight of 20 strands of 1 cm length hair clippings at 0 (before supplementation), 4 and 8 months. The number of hairs of the volunteers in the tocotrienol supplementation group increased significantly as compared to the placebo group, with the former recording a 34.5% increase at the end of the 8-month supplementation as compared to a 0.1% decrease for the latter. Nevertheless, the cumulative weight of 20 strands of hair clippings did not differ much from the baseline for both supplementation groups at the end of the study period. In conclusion, this trial demonstrated that supplementation with tocotrienol capsules increases hair number in volunteers suffering from hair loss as compared to the placebo group. This observed effect was most likely to be due to the antioxidant activity of tocotrienols that helped to reduce lipid peroxidation and oxidative stress in the scalp, which are reported to be associated with alopecia. Kajian telah menunjukkan bahawa terdapat perhubungan di antara oksidatif stres dengan keguguran rambut. Pesakit yang mengalami keguguran rambut secara amnya mempamerkan paras anti-oksidan yang lebih rendah pada kawasan kulit kepala serta index peroksidan lemak yang lebih tinggi. Tokotrienol merupakan vitamin E dan mempunyai efek anti-oksidan yang tinggi. Oleh itu, satu kajian telah dijalankan untuk mengkaji kesan suplementasi tokotrienol ke atas sukarelawan yang mengalami masalah keguguran rambut. Dua puluh satu sukarelawan diagihkan secara rawak untuk menerima 100 mg tokotrienol campuran setiap hari secara oral manakala 17 sukarelawan diagihkan untuk menerima placebo secara oral. Sukarelawan-sukarelawan tersebut dipantau pada bulan ke-0 (sebelum menerima suplementasi tokotrienol), ke-4 dan ke-8 bagi menentukan bilangan rambut pada kawasan kepala yang telah ditentukan terlebih dahulu serta berat 20 helai keratan rambut sepanjang 1 cm. Sukarelawan-sukarelawan yang menerima suplementasi tokotrienol menunjukkan peningkatan bilangan rambut yang signifikan berbanding kumpulan placebo. Kumpulan suplementasi tokotrienol mencatatkan peningkatan sebanyak 34.5% pada penghujung bulan ke-8 berbanding dengan penurunan sebanyak 0.1% yang dicatatkan oleh kumpulan placebo. Namum demikian, berat 20 helai keratin rambut tidak banyak berbeza di antara kedua-dua kumpulan pada penghujung tempoh kajian. Sebagai kesimpulan, kajian ini menunjukkan bahawa suplementasi dengan kapsul tokotrienol meningkatkan bilangan rambut pada sukarelawan yang mengalami masalah keguguran rambut berbanding dengan kumpulan placebo. Kesan ini berkemungkinan disebabkan oleh aktiviti anti-oksidan tokotrienol yang membantu menurunkan peroksidan lemak dan oksidatif stres pada kulit kepala, dimana kedua-duanya telah dihubungkaitkan dengan keguguran rambut.